2005
DOI: 10.1159/000083529
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol: Association with Mortality and Hospitalization in Hemodialysis Patients

Abstract: Background/Aims: Hypocholesterolemia is a common finding in hospitalized elderly people, critically ill surgical patients, septic patients and end-stage renal disease patients. The different effect of lipid subfractions on patients with end-stage renal disease has never been demonstrated. We aim to study the effect of lipid subfractions on hospitalization and mortality in maintenance hemodialysis (MHD) patients. Methods: Lipid subfractions, including total cholesterol (TC), triglycerides (TG), high-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
3
23
2
Order By: Relevance
“…In previous investigations, chronic dialysis patients frequently have low HDL-C and LDL-C levels than the general population and predict worse all-cause outcomes (14,15). Although the prevalence of dyslipidemia is extremely high in dialysis patients, the exact relationship of fetuin A and dyslipidemia in these patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations, chronic dialysis patients frequently have low HDL-C and LDL-C levels than the general population and predict worse all-cause outcomes (14,15). Although the prevalence of dyslipidemia is extremely high in dialysis patients, the exact relationship of fetuin A and dyslipidemia in these patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid abnormalities are characterized by high TC, a moderate hypertriglyceridemia, high LDL cholesterol and low HDL cholesterol, predicting poor outcomes in patients on chronic HD with high infection-related mortality (Prichard, 2003;Chiang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that lipid subfractions, including high total cholesterol (TC), high low-density lipoprotein cholesterol (LDL) and low high-density lipoprotein cholesterol (HDL), predict poor outcome in hemodialysis patients (Prichard, 2003;Chiang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We prospectively established annual mortality and hospitalization indexes as well as collecting patients' demographic and laboratory data since 2002 as mentioned elsewhere (14,15). Among this population, patients with type 2 diabetes were included if their A1C was Ͼ8% at enrollment, despite management with diet alone or with medications (oral hypoglycemic agents or insulin).…”
Section: Research Design Andmentioning
confidence: 99%
“…Plasma adiponectin and interleukin-6 levels were assayed using an enzymelinked immunosorbent assay (R&D Systems, Minneapolis, MN) (5). Serum HBV antigen, anti-hepatitis B surface antibody, and anti-HCV antibody were measured with third-generation enzymelinked immunosorbent assay kits (Abbott, Abbott Park, IL) (14).…”
Section: Study Evaluationsmentioning
confidence: 99%